Workplace health programme among individuals with metabolic syndrome - Chee, Huei Phing; Abu Saad, Hazizi; Mohd Yusof, Barakatun Nisak; Mohd Taib, Mohd Nasir (Emerald Group Publishing, 2015)
Purpose – The purpose of this paper is to ascertain the effect of a physical activity intervention using a combination of Facebook and standing banners on improvements in metabolic syndrome. Design/methodology/approach – In all, 120 (82.8 per cent) government employees with metabolic syndrome completed the programme. A Lifecorder e-STEP accelerometer (Suzuken Company Limited, Nagoya, Japan) was utilized to quantify physical activity. Metabolic syndrome was defined according to “Harmonized” definition at baseline, post-intervention and follow-up. Findings – There were significantly higher step counts in the intervention group as compared to the control group over time. There were significant within-group differences in the step count at the baseline, post-intervention and follow-up assessments (p < 0.001) in both the intervention and control groups. The step count of the intervention group increased by 4,522 steps in the post-intervention assessment compared to the assessment at baseline. The step count of the intervention group in the follow-up assessment was lower than in the post-intervention assessment, but it was still 2,126 steps higher than at baseline. For control group, the difference between the post-intervention assessment and the assessment at baseline was 520 steps per day, while the difference between the follow-up assessment and assessment at baseline was 379 steps per day. The greatest decrease in the percentage of metabolic syndrome was observed in the intervention group, with a reduction of 88.6 per cent in the post-intervention assessment as compared to that at baseline. Research limitations/implications – Future studies should incorporate measures which will be of interest to employers. Greater understanding and assessment of desirable employer-related outcomes are warranted, such as decreased job stress, turnover, absenteeism and improved job satisfaction, productivity and exploration of how these associated with physical activity. Practical implications – The findings show that delivering information on physical activity through an easily implemented and low-cost physical activity intervention via a combination of Facebook and standing banners was successful in improving step counts and metabolic parameters among individuals with metabolic syndrome. Social implications – The findings draw on supporting evidence for advocacy, which is about influencing the larger environment of public policy, and raising awareness of a single programme is insufficient to create lasting social change. Public policy must be shaped in a way that will sustain change across institutions. Originality/value – Despite the well-documented health benefits of physical activity, a growing number of people not achieving the recommended levels of physical activity necessary for good health. Importantly, the study provides a new insight on lifestyle-based physical activity interventions capable of improving step counts and metabolic parameters.